No causal association between the volume of strenuous exercise and coronary atherosclerosis: a two-sample Mendelian randomization study - Xiao, Zijie; Huang, Guolin; Li, Guanhong; Wang, Huihui; Zheng, Xiaoyu; Li, Yongchun; Gong, Fengying; Lv, Ying; Li, Jingjun (Frontiers in Cardiovascular Medicine, 2024)
Objective: Several observational studies have shown that high-volume and high-intensity exercise training increases the prevalence and severity of coronary atherosclerosis, but the causal effect still remains uncertain. This study aims to explore the causal relationship between the volume of strenuous exercise (SE) and coronary atherosclerosis (CA) using the Mendelian randomization (MR) method.The exposure factors were two basic parameters of the volume of strenuous exercise (duration and frequency of strenuous exercise), the outcome factor was coronary atherosclerosis, and the relevant genetic loci were extracted from the summary data of the genome-wide association study (GWAS) as the instrumental variables, and MR analyses were performed using the inverse variance weighting (IVW) method, the weighted median method, and the MR-egger method. Sensitivity analyses were performed using heterogeneity analysis, pleiotropy analysis, and the "leave-one-out" method. The original results were tested using other coronary atherosclerosis data sets.Result: IVW results showed no causal association between duration of strenuous exercise (DOSE) [OR=0.9937, 95% CI (0.9847, 1.0028), P=0.1757] and frequency of strenuous exercise (FOSE) in the last 4 weeks [OR=0.9930, 95% CI (0.9808, 1.0054), P=0.2660] and coronary atherosclerosis. All of the above results were validated with other coronary atherosclerosis data sets.The present study supports that the causal association of duration and frequency of SE with CA was not found, and provides valuable insights into the choice of scientific and correct volume of SE to cardiac rehabilitation (CR).